Filamentation-assisted fourth-order nonlinear process in KTP crystal - 张喜鹏 蒋红兵 陈利 蒋莹莹 杨宏 龚旗煌 (Chinese physics B, 2010)
We present an experimental investigation of a filamentation-assisted fourth-order nonlinear optical process in KTP crystals pumped by intense 1.53 eV （807 nm） femtosecond laser pulses. Femtosecond light pulses at 2.58 eV （480 nm） are generated by the fourth-order nonlinear polarization （p（4） （ω2） = X（4） （ω2, ω, ω, ω, -ω1）E3 （ω）E＊ （ω1）, where E（w） corresponds to the pump frequency and E（wl） to the supercontinuum generated through filamentation）. If the system is seeded by a laser beam at ω1 or ω2 and there are spatial and temporal overlaps with the pump beam, E（ω1） and E（ω2） are simultaneously amplified. When the intensity of the seed laser beam exceeds a certain intensity threshold, the contribution of p（4） （ω） = X（4） （ω, ω1, ω2, -ω, -ω）E（ω1）E（ω2）（E＊ （ω））2 becomes non-negligible, and the amplification weakens. The conversion efficiency from the pump to the signal at 2.58 eV （480 nm） attains to 0.1%.